An effect of physical exercise-induced fatigue on the vital sign parameters: A preliminary study - Zulkifli, Ahmad@Manap; Mohd Najeb, Jamaludin; Kamaruzaman, Soeed (UTM Press, 2019)
Vital sign monitoring is an important body measurement to identify health condition and diagnose any disease and illness. In sports, physical exercise will contribute to the changes of the physiological systems, specifically for the vital signs. Therefore, the objective of this study was to determine the effect of physical fatigue exercise on the vital sign parameters. This is significant for the fitness identification and prediction of each individual when performing an exercise. Five male subjects with no history of injuries and random BMI were selected from students of biomedical engineering, Universiti Teknologi Malaysia. Based on the relationship between physical movement and physiology, the parameters considered were heart rate, blood pressure, and body temperature. Subjects were required to run on the treadmill at an initial speed of 4 km/h with an increase of 1 km/h at every 2 minutes interval. The effect of exercise was marked according to the fatigue protocol where the subject was induced to the maximum condition of performance. All parameters were measured twice, for pre and post exercise-induced protocol. The analysis of relationship of each parameter between pre and post fatigue was p<0.05. The results revealed that the heart rate and gap between blood pressure’s systolic and diastolic were greater for all categories except underweight, where the systolic blood pressure dropped to below 100mmHg at the end of exercise. Also, the body temperature was slightly declined to balance the thermoregulatory system with sweating. Hence, the vigorous physical movement could contribute to the active physiological system based on body metabolism. Heart rate and blood pressure presented significant effects from the fatiguing exercise whereas the body temperature did not indicate any distinguishable impact. The results presented might act as the basis of reference for physical exercise by monitoring the vital sign parameters.